2021
DOI: 10.3390/antiox10121899
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Mushroom Extracts/Polysaccharides—Their Antiviral Properties and Plausible AntiCOVID-19 Properties

Abstract: Mushrooms have been long accomplished for their medicinal properties and bioactivity. The ancients benefitted from it, even before they knew that there was more to mushrooms than just the culinary aspect. This review addresses the benefits of mushrooms and specifically dwells on the positive attributes of mushroom polysaccharides. Compared to mushroom research, mushroom polysaccharide-based reports were observed to be significantly less frequent. This review highlights the antioxidant properties and mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 311 publications
(371 reference statements)
1
26
0
Order By: Relevance
“…Meanwhile, NADH/NADPH oxidase serves as an intracellular ROS source, especially in the vascular tissues and cardiomyocytes (Elahi et al, 2009). The persistence of ROS damages the somatic cells, including the cardiac muscle cells and nerve cells, while the antioxidant properties of the compounds in mushrooms neutralize the ROS (Chun et al, 2021).…”
Section: Mechanism Of Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, NADH/NADPH oxidase serves as an intracellular ROS source, especially in the vascular tissues and cardiomyocytes (Elahi et al, 2009). The persistence of ROS damages the somatic cells, including the cardiac muscle cells and nerve cells, while the antioxidant properties of the compounds in mushrooms neutralize the ROS (Chun et al, 2021).…”
Section: Mechanism Of Oxidative Stressmentioning
confidence: 99%
“…Mushroom extracts can resist free radicals, reduce the activities of pro-inflammatory factors, and relieve chronic inflammation, which are valuable natural antioxidants with the advantages of safety, nontoxic, and easy to obtain (Hu et al, 2021). Some studies have also demonstrated the therapeutic potential of mushroom extract for cardiovascular disease (CAD), neurodegenerative diseases, and cancer (Klupp et al, 2015;Jin et al, 2016;Chun et al, 2021). This review discusses the mechanisms underlying the effect of oxidative stress on chronic inflammation and summarizes the antioxidant properties of compounds purified from mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Total flavonoid content in the ethanolic extract of G. tropicum (29:31 ± 0:38 mg QE/g) was slightly higher than that in C. indica and G. lucidum (Table 2). Polyphenolics are one of the major contributors to the antioxidant properties of mushrooms [7][8][9][10][11][12]. HPLC-DAD system was used for the identification and quantification of polyphenols in the ethanolic extracts of the examined mushrooms species.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, diverse antioxidant compounds have been detected in the Fungi kingdom [ 10 , 11 ]. Mushrooms are widely consumed worldwide as a functional food in fresh as well as processed forms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, interest in the pharmaceutical potential of mushrooms has increased and there is widespread awareness among the educated public. Now, mushrooms are considered as mini-pharmaceutical factories that yield products with miraculous biological properties [34].…”
Section: Medicinal Attributes Of Mushroom Polysaccharidesmentioning
confidence: 99%